Pelatihan Pembuatan Undangan Rapat Digital Pada Organisasi Gerakan Pemuda Ansor Ciledug - Syahriani; Frisma Handayanna; Maryanah Safitri; Tri Santoso (CV. Multi Kreasi Media, 2023)
Ansor Youth is one of the Nahdlatul Ulama groups involved in youth and community affairs. GP Ansor was inaugurated at the 9th NU Congress on April 24 1934 M/10 Muharram 1353 H in Banyuwangi. This organization has proven its existence in various activities such as politics, social and other activities within it. Apart from that, the Ansor Youth Movement organization can announce the quality of their team. Because there are many activities within this organization, the organization often holds internal meetings for the continuity of the organization. This organization still uses manual methods and has not digitized the process of making meeting invitations. Sometimes they make digital meeting invitations, but the design is still not attractive and seems ordinary. For this reason, this community service activity was held to help increase the skills of members or administrators of their organization in making digital-based meeting invitations, so that the meeting invitation becomes an innovative, interesting meeting invitation, does not seem stiff and is more cost-effective and paper-based. Can manage guests who will attend. Apart from that, this activity was held using lecture, demonstration and practicum methods. The results obtained from this activity were that the participants were able to improve their skills in making digital meeting invitations.